Financial innovation, stock market development, and economic growth: An application of ARDL model - Md. Qamruzzaman; Jianguo Wei (International Journal of Financial Studies, 2018)
This study aims to explore the relationship between economic growth, financial innovation, and stock market development of Bangladesh for the period 1980-2016. To investigate long-run cointegration, this study used the autoregressive distributed lagged (ARDL) bounds testing approach. In addition, the Granger-causality test is used to identify directional causality between research variables under the error correction term. Study findings from the ARDL bound testing approach confirm the existence of a long-run association between financial innovation, stock market development, and economic growth. Furthermore, the findings from the Granger-causality test support bidirectional causality between financial innovation, economic growth and stock market development, and economic growth both in the long run and short run. These findings support the theory that market-based financial development and financial innovation in the financial system can spur economic development.
Keywords: O47; P34; D53; O53; 330; ARDL; economic growth; financial innovation; stock market development; Granger-causality